A linear-elastic heuristic-molecular modelling for plane isotropic micropolar and auxetic materials. (1st August 2021) - Casolo, Siro
Abstract: A discrete Lagrangian approach is the basis for modelling the macroscale elastic response of a solid material, which can be homogeneous as well as a periodic composite. The basic topology is a square "heuristic molecule" that is an assemblage of four rigid bodies with a definite shape bonded by elastic springs. This is the minimum unit cell, UC, that contains all the macroscopic mechanical properties of the solid material, object of study. The paper presents 4 unit cells, in progression from a basic molecule bonded by 2 types of central forces, to a refined "Cosserat-auxetic" molecule that is connected by 4 types of shear and central bond-springs. The emphasis is given to the isotropic response in relation to the value of the macroscopic Poisson ratio, and the four examples of UC topologies are presented showing their relationship to different materials at the macro-scale: from a "rari-constant" continuum, through a standard isotropic Cauchy continuum, up to an isotropic centre-symmetric auxetic Cosserat solid.